To Whale or Not to Whale: Repeated Purchase Behavior Paid Players in Genshin Impact - Prilian, Elvin Eka; Dani, Mario; Prameswari, Runi; Manaf, Peri Akbar (International Journal Labs, 2023)
Online games are a means of entertainment for people of all ages and can be easily accessed by anyone. Games or online games that are becoming a trend today are socially interactive video games. These online games invite friends, family, and others to join and participate in ongoing games. This study investigates factors influencing repurchase decisions and intentions among online game players, Genshin Impact, in DKI Jakarta. A quantitative research method was employed, utilizing Partial Least Square with SmartPLS software, and a sample of 500 respondents was analyzed. The variables examined include online game service, game authenticity, social influence, facilitating online conditions, hedonic motivations, price value, habit, repurchase intention, and repurchase decision. The findings reveal that game authenticity, facilitating online conditions, and habit positively influence repurchase intention, while online game services negatively affect it. However, social influence, hedonic motivation, and price value do not significantly impact repurchase intention. In terms of repurchase decisions, facilitating online conditions, hedonic motivation, price value, and repurchase intention have a positive influence, whereas social influence and habit exert a negative effect. Online game services and game authenticity do not significantly influence repurchase decisions. The study also found that repurchase intention mediates the positive impact of game authenticity, facilitating online conditions and habits on repurchase decisions, and the negative impact of online game service on repurchase decisions. However, it does not mediate the effects of social influence, hedonic motivation, and price value on repurchase decisions.